The Challenge of Cultural Diversity: Harnessing a Diversity of Views to Understand Multiculturalism - Nemetz, Patricia L.; Christensen, Sandra L. (Academy of Management Review, 1996)
Patricia L. Nemetz, Sandra L. Christensen, The Challenge of Cultural Diversity: Harnessing a Diversity of Views to Understand Multiculturalism, The Academy of Management Review, Vol. 21, No. 2 (Apr., 1996), pp. 434-462